2015
DOI: 10.1002/em.21963
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of three food processing contaminants in transgenic mice expressing human sulfotransferases 1A1 and 1A2 as assessed by the in vivo alkaline single cell gel electrophoresis assay

Abstract: The food processing contaminants 2‐amino‐1‐methyl‐6‐phenylimidazo[4,5‐b]pyridine (PhIP), 5‐hydroxymethylfurfural (HMF) and 2,5 dimethylfuran (DMF) are potentially both mutagenic and carcinogenic in vitro and/or in vivo, although data on DMF is lacking. The PHIP metabolite N‐hydroxy‐PhIP and HMF are bioactivated by sulfotransferases (SULTs). The substrate specificity and tissue distribution of SULTs differs between species. A single oral dose of PhIP, HMF or DMF was administered to wild‐type (wt) mice and mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Mice orally administered single doses of 900 or 1300 mg/kg showed significant DNA damage of their renal cells, as detected by an alkaline single cell gel electrophoresis assay. Another furan derivative, 2,5 dimethylfuran (DMF), also causes DNA damage in the kidney and the colon [ 69 ]. In an in vitro erythropoietic micronucleus assay, rat bone marrow cells were exposed to DMF at a concentration of 0.1 mM for 1 h. The study indicated that DMF exhibits genotoxicity toward hematopoietic cells [ 53 ].…”
Section: Effects Of Hmf On Human Healthmentioning
confidence: 99%
“…Mice orally administered single doses of 900 or 1300 mg/kg showed significant DNA damage of their renal cells, as detected by an alkaline single cell gel electrophoresis assay. Another furan derivative, 2,5 dimethylfuran (DMF), also causes DNA damage in the kidney and the colon [ 69 ]. In an in vitro erythropoietic micronucleus assay, rat bone marrow cells were exposed to DMF at a concentration of 0.1 mM for 1 h. The study indicated that DMF exhibits genotoxicity toward hematopoietic cells [ 53 ].…”
Section: Effects Of Hmf On Human Healthmentioning
confidence: 99%
“…HMF and furfural are formed as intermediate products of the Maillard reaction and furthermore, HMF is also generated by the caramelization of sugars at high temperature (Morales, 2008). Based on studies in animals, HMF is suspected to have potential genotoxic and mutagenic effects through its metabolism product sulphoxymethylfurfural (Høie et al, 2015) whereas furfural may lead to hepatotoxicity (EFSA, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in an in vitro study, a weak direct genotoxic and mutagenic effect of HMF was found at high molar concentrations [43]. Høie et al [10] examined the effects of hSULT1A1/1A2 on the genotoxicity of HMF and reported that DNA from the kidneys of hSULT mice subjected to HMF treatment showed elevated damage of DNA compared with data from control hSULT animals, but no apparent changes were seen in the kidneys of wild type mice. Moreover, it was found that HMF has a potential effect to induce sister-chromatid alteration at a level of 19.8-3808.0 µM in cells exposed for 32 h [17].…”
Section: Genotoxic and Mutagenic Effectmentioning
confidence: 99%
“…It has been also detected in cigarette smoke and chewing tobacco [4,5]. The toxicological effects of HMF have been demonstrated in several experimental animals and in cultured mammalian cells [6][7][8][9][10]. The daily human intake of HMF was reviewed by Husøy et al [11] and ranged from 30 and 150 mg/person/day, a dose much higher than that of other food heat-borne toxicants like furan and acrylamide [12,13].…”
Section: Introductionmentioning
confidence: 99%